2013
DOI: 10.2147/opth.s39104
|View full text |Cite
|
Sign up to set email alerts
|

The interblink interval in normal and dry eye subjects

Abstract: PurposeOur aim was to extend the concept of blink patterns from average interblink interval (IBI) to other aspects of the distribution of IBI. We hypothesized that this more comprehensive approach would better discriminate between normal and dry eye subjects.MethodsBlinks were captured over 10 minutes for ten normal and ten dry eye subjects while viewing a standardized televised documentary. Fifty-five blinks were analyzed for each of the 20 subjects. Means, standard deviations, and autocorrelation coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 17 publications
1
41
1
Order By: Relevance
“…In previous exploratory studies, we focused first on blink rates, or their reciprocal, IBIs, and the ability to use statistical characteristics of these time-series data to differentiate dry-eye and normal subjects 16. We then began exploring the duration of blinks, finding that abnormally long lid closures appear to occur with greater frequency in dry-eye subjects, and that the IBIs surrounding these long lid closures are modified only in dry-eye subjects 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous exploratory studies, we focused first on blink rates, or their reciprocal, IBIs, and the ability to use statistical characteristics of these time-series data to differentiate dry-eye and normal subjects 16. We then began exploring the duration of blinks, finding that abnormally long lid closures appear to occur with greater frequency in dry-eye subjects, and that the IBIs surrounding these long lid closures are modified only in dry-eye subjects 17.…”
Section: Discussionmentioning
confidence: 99%
“…We study blink and how it is affected by dry eye and visual task, and have recently reported on interblink intervals (IBIs) and their temporal and mathematical characteristics that can be used to differentiate dry-eye and normal subjects 16. We have also focused our attention on the varying patterns of blink, finding that the IBIs surrounding extended blink closures increase significantly in dry-eye subjects 17.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent subject awareness from affecting IBI measurement results, the subjects were video recorded without being informed that the IBI would be measured. Since previous studies have used 10‐ to 15‐minutes periods of VDT work to analyze the IBI and blink rate, and because the subjects may have been distracted at the start of video recording by having the camera immediately in front of their eyes, potentially making the data from this period unreliable, the 20‐minute period from 40 minutes to 60 minutes after the start of VDT work was used for the IBI study. The number of times subjects engaged in BW, the duration of each period of BW, and the total BW time were also measured during the final 20‐minute period.…”
Section: Methodsmentioning
confidence: 99%
“…For example, some smartphone applications include the evaluation of subjective symptoms called Ocular Surface Disease Index (OSDI) questionnaire [13]. Other applications use the smartphone camera and measure visual function [14] or interblink interval [15] that are associated with severity of dry eye. However, these applications cannot evaluate tears directly.…”
Section: Related Workmentioning
confidence: 99%